Front cover: Focusing surface acoustic waves assisted electrochemical detector in microfluidics. Issue 10 (2nd June 2020) - Zheng, Tengfei; Liu, Yue; Xu, Chaoping; Lu, Haiwei; Wang, Chaohui
Abstract : DOI: 10.1002/elps.201900315 The cover picture shows the application of Focusing Surface Acoustic Waves (FSAWs) for enhancing the electrochemical detector sensitivity in open microfluidics. Two paralleled FSAWs are generated on the piezoelectric substrate and remarkably improve the liquid mixing rate by forcing fluid to move microfluidically. The improvement in liquid mixing can significantly increase the sample diffusion rate and the oxidation current in three‐electrode systems. The idea can be extended to detect ions with low reagent and sample consumption, rapid analysis and low waste in micro total analysis systems.